Drug targeting of one or more aminoacyl-tRNA synthetase in the malaria parasite Plasmodium falciparum. Issue 6 (June 2018) - Manickam, Yogavel; Chaturvedi, Rini; Babbar, Palak; Malhotra, Nipun; Jain, Vitul; Sharma, Amit
Highlights: Malaria remains a killer disease and drug resistance poses a growing problem. Aminoacyl tRNA synthetases (aaRSs) are essential housekeeping enzymes. Parasite aaRSs are excellent targets and several inhibitors have been identified. The aaRSs have numerous subsites per enzyme that are druggable. Unexplored parasite aaRSs can be screened for new classes of drug-like molecules. Abstract : Malaria remains a major infectious disease and, despite incidence reduction, it threatens resurgence in drug-resistant forms. Antimalarial drugs remain the mainstay of therapeutic options and hence there is a constant need to identify and validate new druggable targets. Plasmodium falciparum aminoacyl-tRNA synthetases ( Pf- aaRSs) drive protein translation and are potent targets for development of next-generation antimalarials. Here, we detail advances made in structural-biology-based investigations in Pf- aaRSs and discuss their distribution of druggable pockets. This review establishes a platform for systematic experimental dissection of malarial parasite aaRSs as a new focus for sustained drug development efforts against malaria.